EphA2 promotes tumorigenicity of cervical cancer by up‐regulating CDK6. Issue 6 (14th February 2021) - Huang, Changhao; Chen, Zihua; He, Yihong; He, Zhengxi; Ban, Zhenying; Zhu, Yuanhang; Ding, Leilei; Yang, Chen; Jeong, Ji‐Hak; Yuan, Weijie; Yang, Li
Abstract: Erythropoietin‐producing hepatocellular receptor A2 (EphA2) receptor tyrosine kinase plays an important role in tissue organization and homeostasis in normal organs. EphA2 is overexpressed in a variety of types of solid tumours with oncogenic functions. However, the role of EphA2 in cervical cancer (CC) is still needed to be further explored. Here, we examined the role of EphA2 by establishing a stable EphA2 knock‐down CC cell lines or a stable EphA2‐overexpressed CC cells lines. Overexpression of EphA2 increased cell proliferation and migration of CC while EphA2 knock‐down decreased the CC tumorigenicity. In addition, EphA2 knock‐down suppressed CC tumour development in the xenograft mouse model. Inhibition of EphA2 by AWL‐II‐41‐27, EphA2‐specific tyrosine kinase inhibitor, or knock‐down of EphA2 decreased mRNA and protein expression of cyclin‐dependent kinase (CDK) 6 in CC cells, which increased cellular susceptibility to epirubicin (EPI), an anti‐cancer chemotherapy drug. A clinicopathological study of EphA2 was conducted on a cohort of 158 human CC patients. EphA2 protein expression was positively correlated with CDK6 protein expression, invasion depth, lymph node metastasis and clinicopathological stage ( P  < .05). This study demonstrates the oncogenic activity of EphA2 in vitro and in vivo, which provides insights into the relevant mechanisms that might lead to novel treatments for CC.